(untitled) (International Journal of Physiotherapy, 2025)
Background: Acute motor axonal neuropathy (AMAN) is an autoimmune disorder that targets the axons of motor neurons without significant demyelination or sensory involvement. It primarily affects the lower motor neurons, leading to muscle weakness and diminished reflexes. It is a subtype of Guillain-Barre syndrome. Acute Motor Axonal Neuropathy (AMAN) in children shares similarities with adult presentations but also shows unique characteristics due to developmental and physiological differences. It typically appears after the third year of life. Case Summary: A 6-year-old male child was reported to the emergency room with ascending weakness, drooling of saliva, and difficulty in breathing, along with flaccid tetraplegia and areflexia. An electrophysiological examination showed severe motor axonal neuropathy. Interventions: A progressive program is designed using functional exercises. These are as follows: Functional Training, Cardio-respiratory Training, Balance Training, and Coordination Training. Exercises progressed from passive ROM through gravity-eliminated AROM and antigravity-AROM to resisted functional exercises. Outcome measures: The outcome measures are, Muscle Strength using Manual Muscle Testing (MMT); Disability and Progression of the disease using the Overall Neuropathy Limitation Scale (ONLS) and Hughes Severity Scale; Cardiorespiratory fitness using Borg Rating of Perceived Exertion (Original); (BBS); Mobility using Dynamic Gait Index (DGI). Conclusion: Hence, structured and supervised exercises, including supervised cycling or prescribed unsupervised exercises and aerobic activities, have significantly improved strength, balance, gait, and cardiorespiratory functions.